How has the European Monetary Integration Process Contributed to Regional Financial Market Integration? - Beate Reszat (Hamburg Institute of International Economics (HWWA), 2003)
European monetary integration was one element in the process of financial market integration but by far not the only one. The paper traces the development of financial markets and systems in Europe from the beginnings of the euromarkets in the 1950s over early exchange rate arrangements and the establishment of the Single Market program to the launch of the euro and its effects. Not surprisingly, the contribution of the common currency to financial integration has been the stronger the more national markets have in common and the greater the importance of currency risk as discriminating factor. It has been most successful in the interbank market for very short-term unsecured deposits and in markets for bonds and derivatives, and played a lesser role for collateralised instruments and equities where differences in institutions and systems as well as cultural aspects impose stronger impediments. Experience has shown that in the process of financial integration a common currency is no substitute for the removal of institutional barriers and other obstacles hindering the free move of financial institutions and services. And, it cannot compensate for the specific information about individuals, firms and products required in some market segments that is a lasting impediment to full integration.
Keywords: F33; G15; E42; 330; Monetary Standards and Regimes; International Monetary Arrangements and Institutions; International Financial Markets; Europäische Wirtschafts- und Währungsunion; Finanzmarkt; Internationaler Finanzmarkt; Marktintegration; Geschichte; EU-Staaten